1977
DOI: 10.1152/ajpheart.1977.232.1.h35
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of increasing airway pressure in the dog

Abstract: In paralyzed anesthetized dogs the cardiovascular effects of increasing positive end-expiratory pressure (PEEP) were explored under two conditions: a) end-expiratory lung volume increasing, b) end-expiratory lung volume kept nearly constant by matching pleural pressure rise to end-expiratory airway pressure rise. Two series of experiments were done: I) xenous return was allowed to fall, II) venous return was kept constant by infusion of volume. Right atrial pressure, pulmonary arterial pressure, and left atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
3

Year Published

1979
1979
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 22 publications
3
32
0
3
Order By: Relevance
“…Qvist et al (1975) have shown that CPPV can decrease cardiac output for up to 8 hours. Furthermore, several investigators (Marotta and Harner, 1962;Maulsby and Hoff, 1962;Wong et al, 1967;Scharf et al, 1977) have demonstrated that bilateral cervical vagotomy, which interrupts most afferent nerve fibers from the lungs, does not alter the cardiovascular response to CPPV. It is likely, then, that CPPV decreases cardiac output primarily by reducing right and left ventricular end-diastolic volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qvist et al (1975) have shown that CPPV can decrease cardiac output for up to 8 hours. Furthermore, several investigators (Marotta and Harner, 1962;Maulsby and Hoff, 1962;Wong et al, 1967;Scharf et al, 1977) have demonstrated that bilateral cervical vagotomy, which interrupts most afferent nerve fibers from the lungs, does not alter the cardiovascular response to CPPV. It is likely, then, that CPPV decreases cardiac output primarily by reducing right and left ventricular end-diastolic volumes.…”
Section: Discussionmentioning
confidence: 99%
“…If this were true, the effective or transmural filling pressure of the right atrium (right atrial pressure minus pleural pressure) would be expected to decrease during CPPV. However, several investigators have reported that transmural right and left atrial pressures, measured rel- ative to lateral pleural or esophageal pressure, do not decrease, but stay the same or actually increase during CPPV (Scharf et al, 1977;Zarins et al, 1977;Cassidy et al, 1978). This suggests that decreased venous return is not the primary factor producing the decrease in cardiac output.…”
mentioning
confidence: 99%
“…The methods used in this study have been previously used to describe the circu latory changes accompanying the use of positive end-expiratory pressure [22], me chanical positive pressure ventilation [24], and inspiratory loading [20]. In this study, we could not calculate left ventricular volume, since only 2 of the 3 required left ventricular dimensions were measured.…”
Section: Discussionmentioning
confidence: 99%
“…It was expressed in arbitrary units and normalized by dividing by the control value. For the measurement o f Ppl, a brass cannula, previously described [22], 0.25 cm in diameter, was inserted through the chest wall into the left hemithorax. Fluid-Filled catheters (Cordis No.…”
Section: Methodsmentioning
confidence: 99%
“…Our interest in reflex cardiovascular effects of lung hyperinflation arose as a consequence of observations that ventilation with positive end-expiratory pressure that hyperinflates the lung, depresses cardiac output beyond that attributable to mechanical obstruction either to venous return or to pulmonary circulation (1)(2)(3)(4). To study reflex cardiovascular effects of lung hyperinflation, it is necessary to employ a model in which the direct mechanical effects of lung inflation are eliminated.…”
Section: Introductionmentioning
confidence: 99%